IMPLEMENTASI PROGRAM GERAKAN BANTUL BERSIH SAMPAH 2025 (STUDI KASUS PELAKSANAAN BANK SAMPAH DI KALURAHAN SITIMULYO KAPANEWON PIYUNGAN) - Widyastuti, Anna; Yulianto, Daris (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
The implementation of the Bantul Clean Waste Movement 2025 program is an initiative to reduce waste in Bantul Regency, focusing on the implementation of waste banks in Sitimulyo Village, Piyungan Sub-district. This research aims to understand the implementation and factors affecting the Bantul Clean Waste Movement 2025 program, using a case study on the implementation of waste banks in Sitimulyo Village, Piyungan Sub-district. This study uses a qualitative approach with descriptive methods, and data is collected through interviews, observations, documentation, and literature studies, with informants selected through purposive sampling. The three goals of the Bantul Clean Waste Movement 2025 are used to measure the program's implementation, namely reducing waste from its source, which is households, managing waste at the village level, and minimizing the amount of waste sent to the Piyungan landfill. Meanwhile, to measure the influencing factors, George C. Edward’s theory in Agustino (2014: 150) is used, focusing on communication, resources, disposition, and bureaucratic structure. The results of the research show that despite challenges in community participation and resource management, the program has successfully increased environmental awareness, provided economic benefits to the community, and contributed to reducing the volume of waste sent to the Piyungan landfill.